Effects of fullerenol nanoparticles and amifostine on radiation-induced tissue damages: Histopathological analysis - Jacevic, Vesna; Jovic, Danica; Kuča, Kamil; Dragojevic-Simic, Viktorija; Dobric, Silva; Trajkovic, Sanja; Borisev, Ivana; Segrt, Zoran; Milovanovic, Zoran; Bokonjic, Dubravko; Djordjevic, Aleksandar (Journal of Applied Biomedicine, 2016)
Fullerenol C60(OH)24 nanoparticles (FNP) are promising radioprotectors in prevention of early and late ionizing radiation injury. The aim of this study was to compare the efficacy of FNP and amifostine (AMI) in protection of rats exposed to whole-body X-ray irradiation (7 or 8 Gy). Both compounds (FNP, 100 mg/kg ip; AMI, 300 mg/kg ip) were given 30 min before irradiation throughout the study. The general radioprotective efficacy of FNP and AMI were evaluated in rats irradiated with an absolutely lethal dose of X-rays (8 Gy) and their survival were monitored during the period of 30 days after irradiation. Both compounds were of comparable efficacy. Tissue-protective effects of tested compounds were assessed in rats irradiated with an sublethal dose of X-rays (7 Gy). For this purpose, the animals were sacrificed on the 7th and 28th day after irradiation. Their lung, heart, liver, kidney, small intestine and spleen were taken for histopathological and semiquantitative analysis. Careful examination of established tissue and vascular alteration revealed better radioprotective effects of FNP compared to those of AMI on the small intestine, lung and spleen, while AMI had better radioprotective effects than FNP in protection of the heart, liver and kidney. Results of this study confirmed high radioprotective efficacy of FNP in irradiated rats that was comparable to that of AMI, a well-known radioprotector.
Keywords: Radiation-Protective Agents; experimentální radiační poranění; Amifostine; modely u zvířat; Nanotubes; Nanoparticles; Radiation Injuries; fullereny; radiační ochrana; nanočástice; Radiation Dosage; Lethal Dose 50; Fullerenes; potkani Wistar; amifostin; radiační poranění; Rats, Wistar; Radiation Injuries, Experimental; Models, Animal; mužské pohlaví; zvířata; Radiation Protection; LD50; nanotrubičky; Animals; radioprotektivní látky; Male; dávka záření